The “QT Clock” to Improve Detection of QT Prolongation in Long QT Syndrome Patients - Page, Alex (Heart Rhythm, 2015)
BACKGROUND: The QT interval is a risk marker for cardiac events such as TdP. However, QT measurements obtained from a 12-lead ECG during clinic hours may not capture the full extent of a patient’s daily QT range. OBJECTIVE: We evaluated the utility of 24-hour Holter ECG recording in patients with long QT syndrome to identify dynamic changes in the heart-rate corrected QT interval, and we investigated methods of visualizing the resulting data sets. METHODS: Beat-to-beat QTc (Bazett) intervals were automatically measured across 24-hour Holters from 202 LQT1, 89 LQT2, 14 LQT3 genotyped patients and a reference group of 200 healthy individuals. We measured the percentage of beats with QTc greater than the gender-specific threshold (QTc>470ms in women and QTc>450ms in men). The percentage of beats with QTc prolongation was determined across the 24-hour recordings. RESULTS: Based on the median percentage of heart beats per patient with QTc prolongation, LQT1 patients showed more frequent QTc prolongation during the day (~3PM) than they did at night (~3AM): 97% vs. 48%, p~10(−4) for men, 68% vs. 30%, p~10(−5) for women. LQT2 patients showed less frequent QTc prolongation during the day, compared to nighttime: 87% vs. 100%, p~10(−4) for men, 62% vs. 100%, p~10(−3) for women. CONCLUSION: In patients with genotype positive LQTS, significant differences exist in the degree of daytime and nocturnal QTc prolongation. Holter monitoring using the “QT clock” concept may provide an easy, fast, and accurate method to assess the true personalized burden of QTc prolongation.